Association Between agr Type, Virulence Factors, Biofilm Formation and Antibiotic Resistance of Staphylococcus aureus Isolates From Pork Production - Zhang, Yang; Xu, Dongyang; Shi, Lei; Cai, Rujian; Li, Chunling; Yan, He (Frontiers in Microbiology, 2018)
Livestock-associated S. aureus colonization and/or infections exist in pigs and people in frequent contact with pigs. In this study, a total of 130 S. aureus isolates obtained from different stages of pork production were subjected to antimicrobial susceptibility, biofilm formation, as well as PCR screening to identify virulence genes, and the accessory gene regulator alleles (agr). Among all 130 S. aureus isolates, 109 (83.8%, 109/130) isolates were positive for agr. All swine farms isolates belonged to agr IV, whereas S. aureus isolated from slaughterhouse and retail indicated diverse agr types. All isolates exhibited biofilm formation ability, and raw meat isolates (belonging to agr I) exhibited a greater ability to form strong biofilms than swine farms isolates (belonging to agr IV). Agr-positive isolates were associated with more virulence genes than agr-negative isolates. Most biofilm-producing isolates were positive for microbial surface component recognizing adhesive matrix molecule (MSCRAMM), capsule type and ica group genes. The results illustrate a significant association between the prevalence rate of MSCRAMM, capsule type and ica group genes among isolates producing weak, moderate and strong biofilms. The high prevalence of resistance to ciprofloxacin, gentamicin, tetracycline, clarithromycin, clindamycin and trimethoprim-sulfamethoxazole were mainly observed in moderate and weak biofilm producers. Our findings indicate that S. aureus isolates from pork production displayed diverse molecular ecology.